Pengaruh FDI Dan Kontribusi Sektor Jasa Terhadap Penerimaan Pajak Dengan Pemoderasi Kualitas Peraturan - Wahyuni, Desak Ari Gita; Wijaya, Suparna (PT Wim Solusi Prima, 2023)
According to several reports from the international monetary authority, countries belonging to Sub-Saharan Africa still maintain their tax ratio below the threshold of 15%. In fact, the structure of tax revenues in many of these countries has improved in several periods. The slow growth of domestic revenue mobilization, the increase in the debt-to-GDP ratio and the occurrence of a budget deficit are clear manifestations that the tax policy needs to be reformed. This study focuses on analyzing the relationship between Foreign Direct Investment (FDI), the contribution of the Service Sector and the ratio of tax revenues in 33 countries in Sub Saharan Africa during the 2002-2019 period. Through a quantitative approach, this study uses multiple linear regression methods on panel data with the Fixed Effect Model estimation. The research results strongly state that all dependent variables can be explained by the independent variable by 89.19%. As independent variables, FDI and the contribution of the service sector are moderated by the regulatory quality variable. The conclusion stated FDI has a significant positive effect on tax revenues. However, the contribution of the service sector has a negative coefficient values but does not have a significant effect on tax revenues. This study also uses government effectiveness and the industrial sector's contribution to GDP as control variables.